Wyniki symulacji kanału ogólnospławnego w ul. P. Skargi w Głogowie = Simulation results of P. Skargi street combined sewage channel?s in Głogów - Nowak, Agnieszka; Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an analysis of P. Skargi street channel overload with combined sewages using EpaSWMM model and results obtained in flowmeter and pluviometer measurement systems in Głogów. The influence of obtained simulation results and depth measurement system has been shown.
Keywords: kanalizacja ogólnospławna; modelowanie; monitoring opadów; monitoring przepływów; combined sewer systems; modeling; rainfall monitoring; flowrate monitoring